How the Waltz was Won Transmutations and the Acquisition of Style in Early English Modern Ballroom Dancing. Part One: Waltzing Under Attack - Buckland, Theresa Jill (Edinburgh: Edinburgh University Press, 2018)
RESUMEN: This two-part article examines the contested transition in London's fashionable ballrooms from the established Vitorian rotary waltz to the modern English waltz of the early 1920s. Existing scholarship on the dance culture of this period and locale has tended to focus on issues of national identity, gender, race, class and the institutionalisation of popular dance practices. Although these are of profound significance and are here integrated into the analysis, this fresh study focuses on the waltz's choreological aspects and relationship to its ballroom companions; on the dance backgrounds and agency of the waltz's most influential practitioners and advocates, and on the fruitful nexus between theatre, clubs, pedagogy, the press and competitions in transforming style and practice towards modern English ballroom dancing as both a social and artistic form. Part One discusses the kinetic problems that waltzing couples encountered in the face of ragtime dances and tango, the impact of World War One on social dance practices in fashionable London and the response of the press and the dance pedagogic profession to the post-war dance craze. Improvisational strategies are considered as contributory factors in the waltz's muted persistence throughout the war while throwing light on how certain social choreomusical practices might lead to the transmutation of dance into newly recognized forms. The persuasive role of London-based leaders such as Philip Richardson, Madame Vandyck and Belle Harding in these early years of modern ballroom dancing is brought to fresh attention. Part One concludes with the dance teachers' inconclusive attempts during 1920-21 to define and recommend a waltz form compatible with both a discrete choreomusical identity and the stylistic dictates of modern ballroom dancing. PALABRAS CLAVE: English Waltz, modern ballroom dancing, social dance, improvisation, Fisrt World War, pedagogic control, Philip Richardson